A Comparative Legal Analysis of Village Head Term Extensions within the Framework of Indonesia’s Democratic Rule of Law - Agustini , Ninik; Sariono, Joko Nur; Salviana, Fries Melia (International Journal of Business, Law, and Education, 2025)
The extension of village head terms under Law Number 3 of 2024 has generated significant debate within the context of Indonesia’s democratic rule of law. This amendment changes the previous six-year term for a maximum of three periods to an eight-year term for a maximum of two periods. This article aims to analyze the ratio legis underlying the extension and assess its compatibility with constitutional principles governing democratic governance and the limitation of executive power. Employing a normative juridical method with statutory and conceptual approaches, this study examines the legal framework and democratic implications of the revised provision. The findings reveal that the government’s justification centers on budgetary efficiency, enhanced continuity of development programs, and political stability within village communities. Nevertheless, these rationales are predominantly pragmatic and insufficient when measured against democratic safeguards. The reduced frequency of elections may weaken public oversight, limit leadership circulation, and heighten the risk of power abuse—conditions exacerbated by the high incidence of corruption in village administrations reported by Indonesia Corruption Watch (ICW). Moreover, the policy contradicts the post-1998 reform spirit, which emphasized term limits to prevent authoritarian tendencies. Therefore, the extension requires comprehensive reevaluation to ensure it aligns with democratic values, maintains accountability, and upholds the principles of the rule of law.